ChemInform Abstract: Catalytic Stereoselective Cascade Reactions of Quinols with Trifluoromethyl Ketones: Direct Access to CF3‐Containing 1, 3‐Dioxolanes. Issue 34 (4th August 2016) - Li, Feng; Wang, Jingjing; Xu, Mengmeng; Zhao, Xiaobo; Zhou, Xiaohong; Zhao, Wen‐Xian; Liu, Lantao
Abstract: The products are obtained in high yields and with moderate to high diastereoselectivities.